Factors Affecting the Effectiveness of the UC Reward System Toward a Sustainable Motivation Framework for Student Success - Dave B. Polistico (Future Science / FSH-PH Publications, 2026)
Reward systems are commonly applied in tertiary institutions, although their effectiveness in maritime colleges has seldom been empirically evaluated. In this study, the UC Reward System, an academic incentives scheme implemented at the University of Cebu Maritime Education and Training Center for almost two decades, is analyzed in terms of its effectiveness and its external variables in relation to the academic perseverance and academic performance of third-year cadets. The quantitative descriptive-correlational approach was used. Survey questionnaire and document review of the academic records of 236 third-year cadets served as sources of data, with the use of Pearson product-moment correlation to analyze the relationships among the variables. Cadets regarded the reward system as effective, more so in its performance aspect than its perseverance aspect. However, the results of the correlations yielded a different finding, with only the perseverance-oriented aspect of perceived effectiveness significantly correlated with actual perseverance behavior, but not with academic performance. As for the factors, intrinsic motivation and institution-related factors were found to be significantly related to academic perseverance, while extrinsic motivation, despite having the highest endorsement score of all motivational orientations, is not significantly related to any of the outcomes. Institution-related factors, on the other hand, is the sole variable significantly related to both outcomes. It may be concluded that the institutional context around a reward system makes for greater contribution to cadet outcomes compared to the motivational orientations of the cadets.